The investigation of the effects of Ramadan fasting on the mood state of healthy volunteer persons - Ozgur Erdem (SERNEV, 2018)
Introduction: The present study was carried out to investigate the effect of Ramadanfasting on human psychology among healthy volunteer people.Methods: In this cross-sectional type study, the universe of the research iscomposed of healthy volunteer people who registered at the Kayapınar Peyasfamily health centre in Diyarbakır and declared they planned to fast at themonth of Ramadan in 2017. A questionnaire form including a sociodemographicquestionnaire and Turkish version of the Depression Anxiety Stress Scale(DASS-42) was formed. The online questionnaire technique was used to obtain thedata via e-mail and smartphone. The study was conducted during the summer of2017. The survey conducted to the same healthy volunteer group one weak beforeRamadan (May 22-26) and at the end of Ramadan (June 21-25). SPSS 21.0statistical package was used in the data analysis. The statistical analyseswere considered significant if p lt;0.05.Results: 73 healthy volunteer subjects with no known health problems and whowere not in the risk groups in terms of mental and physical health wereincluded in the statistical evaluation. According to the DASS score, when thepre-Ramadan scores of the samples were compared to the post-Ramadan scores;depression (p=0.001), anxiety (p=0.01) and stress (p =0.002) scores were foundto be lower at the end of Ramadan. When compared to the pre-Ramadan scores ofthe samples and the post-Ramadan scores; anxiety (p lt; 0.05) prevalence wasfound to be lower at the end of Ramadan.Conclusion: The results of the current study demonstrated that fasting in themonth of Ramadan have been effective in diminishing stress, anxiety, anddepression levels.